2010
DOI: 10.1136/bcr.05.2010.3035
|View full text |Cite
|
Sign up to set email alerts
|

Unusual mechanism of tendoachilles injury

Abstract: SummaryA 67-year-old woman sustained electric shock while using her hair dryer. During this process her left leg shot up in the air following which she could not walk properly with that leg. She attended the accident and emergency and, considering a possibility of an undisplaced fracture of the calcaneum, she was referred to the fracture clinic the next day. She was clinically diagnosed to have tendoachilles rupture and this was further confirmed by an ultrasound scan. Predisposing factors like drug intake or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Early weight-bearing exercises should be given to decrease tendon elongation, improve the mechanical properties of tendons, and improve functional outcomes [ 19 ]. After radiological investigations, the patients are usually prescribed surgical treatment due to high-grade trauma [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Early weight-bearing exercises should be given to decrease tendon elongation, improve the mechanical properties of tendons, and improve functional outcomes [ 19 ]. After radiological investigations, the patients are usually prescribed surgical treatment due to high-grade trauma [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…In that case, a woman experienced a shock while blow drying her hair, causing her to jerk her leg uncontrollably and rupture her tendon. 9 …”
Section: Discussionmentioning
confidence: 99%
“…Butler and Gant et al [17] reported only one case of a rupture of the long head of biceps tendon, which was related to the electrical injury in their series with 188 patients. Bhaskaran and Dharmarajan [18] reported a 67-year-old woman with Achilles tendon rupture after exposing electrical shock while using a hairdryer. The late rupture of the flexor profundus of the index finger has also been defined over 15 years after electrical injury [19].…”
Section: Discussionmentioning
confidence: 99%